2003
DOI: 10.5713/ajas.2003.880
|View full text |Cite
|
Sign up to set email alerts
|

The Use of High-oil Corn in Young Broiler Chicken Diets

Abstract: The objective of this study was to measure performance of young broiler chickens fed three varieties of high-oil corn (HOC 1, 2, and 3) compared with eight varieties of normal corn (NC). HOC varieties contained about 80% more oil than NC (average crude fat; 6.71% vs 3.72%) and about 29% more protein (average CP; 9.54% vs 7.38%). Each experimental diet was formulated with the same amount (55.205%) of each corn hybrid. Experiment 1 had by six dietary treatments (HOC1 and five NC varieties, 360 chickens) and Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…The feeding value of high-oil corn for raising egg-type chickens, (Han et al, 1987;Parsons et al, 1998) and broilers (Han et al, 1987;Adams et al, 1994;Bartov and Barzur, 1995;Benitez et al, 1999;Kim and Allee, 2003) has been well documented. In these previous studies, it was concluded that high-oil corn had greater nutritional value in comparison with yellow corn.…”
Section: Introductionmentioning
confidence: 99%
“…The feeding value of high-oil corn for raising egg-type chickens, (Han et al, 1987;Parsons et al, 1998) and broilers (Han et al, 1987;Adams et al, 1994;Bartov and Barzur, 1995;Benitez et al, 1999;Kim and Allee, 2003) has been well documented. In these previous studies, it was concluded that high-oil corn had greater nutritional value in comparison with yellow corn.…”
Section: Introductionmentioning
confidence: 99%